The Effectiveness of Comic-Based Learning Media in Enhancing Arabic Language Achievement Among Elementary Madrasah Students - Fauzan Kamal Fahmi; Ahmad Nur Mizan; Zulhannan (Yayasan Darussalam Bengkulu, 2025)
This study aims to describe the effectiveness of comic-based media in enhancing Arabic language learning among fifth-grade students at MIN 3 Pringsewu. The findings reveal that comic media is an effective tool for improving students’ learning outcomes in Arabic. This is evidenced by the calculated N-Gain score, where the experimental class achieved an average of 61.43, categorized as moderate, while the control class obtained an average Gain Score of 16.49, categorized as low. These results indicate that the development of comic-based instructional media is effective for classroom implementation. Furthermore, the effectiveness of using comics is reflected in the improvement of students’ pretest and posttest scores. The pretest average score of students in the experimental class prior to using thematic comics was 57.87, which increased to 78.51 after implementation. In comparison, the control class scored 55.57 in the pretest and 61.92 in the posttest. The statistical analysis shows that the posttest data between the two groups yielded a t-value significance of 0.000, indicating a significant difference since Sig. (2-tailed) < 0.05 and the t-value was positive, leading to the rejection of H0. All of these data substantiate the conclusion that comic-based media effectively enhances Arabic language learning for fifth-grade students at MIN 3 Pringsewu. Therefore, it can be concluded that there is a significant positive impact of using comics as an instructional medium on students’ learning achievement in Arabic.